Frontier Computing Theory, Technologies and Applications - Hung, Jason C.; Yen, Neil Y.; Li, Kuan-Ching (Lecture Notes in Electrical Engineering, 2016)
This volume contains the proceedings of the 4th International Conference on Frontier Computing (FC 2015), Bangkok, Thailand, September 9-11, 2015, and brings together state-of-the-art results covering many aspects of emerging computer science and information technology from international academic and industrial researchers. FC 2015 aimed at providing an open forum to reach a comprehensive understanding of the recent advances and developing trends in information technology, computer science and engineering, with themes under the scope of communication networks, business intelligence and knowledge management, web intelligence, and any related fields that prompt the development of information technology. Contributions cover a wide spectrum of topics: database and data mining, networking and communications, web and internet of things, embedded system, soft computing, social network analysis, security and privacy, optics communication, and ubiquitous/pervasive computing. Many papers have shown great academic potential and value, and in addition indicate promising directions of research in the focused realm of this conference series. Readers, including students, researchers, and industry professionals, will benefit from the results presented in this book, and it provides indicators for emerging trends for those starting their research careers. .